Rachels Klage im antiken Judentum und frühen Christentum : eine auslegungsgeschichtliche Studie - Ritter, Christine. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 2003)
Study of the exegesis of the Old Testament tradition on the matriarch Rachel. The centre of the study is Rachel's complaint in Jeremiah 31.15-17. After an analysis of the Old Testament texts, the reception of these traditions in ancient translations in the Pseudepigrapha, in Philo of Alexandria, in Flavius Josephus as well as in the New Testament is investigated. The main part of the study is represented by source material in the Rabbinic literature. The study is concluded by an overview of the interpretation of the Rachel figure in patristic literature. The sources containing the Rachel traditions are, in part, hard to access. The source material on Rachel is presented and analyzed, in order to make the plethora of interpretations accessible to a wider audience, especially the Rabbinic interpretations.